The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/cam4.173
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 disruption impaired tumoral angiogenesis by reducing VEGF secretion from TGFβ1‐induced macrophages

Abstract: In order to study the role of galectin-3 in tumor angiogenesis associated with tumor-associated macrophages (TAM) and tumor parenchyma, the galectin-3 expression was reconstituted in Tm1 melanoma cell line that lacks this protein. Galectin-3-expressing cells (Tm1G3) and mock-vector transfected cells (Tm1N3) were injected into wild-type (WT) and galectin-3 knockout (KO) C57Bl/6 mice. Tumors originated from Tm1G3 were larger in tumor volume with enlarged functional vessels, decreased necrotic areas, and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 47 publications
(67 reference statements)
0
37
0
10
Order By: Relevance
“…Gal-3 is secreted into tumor stroma and plays an important role of tumor microenvironment contributing to the tumor progression. Gal-3 also affects the tumor angiogenesis by regulating vascular endothelial growth factor [135].…”
Section: Gal-3 In Tumor-associated Macrophagesmentioning
confidence: 99%
“…Gal-3 is secreted into tumor stroma and plays an important role of tumor microenvironment contributing to the tumor progression. Gal-3 also affects the tumor angiogenesis by regulating vascular endothelial growth factor [135].…”
Section: Gal-3 In Tumor-associated Macrophagesmentioning
confidence: 99%
“…The last four are important steps of the metastatic process, in which extracellular, rather than intracellular galectin-3, plays a prominent role in both tumor cells and stromal cells present in the tumor microenvironment (19, 2628). …”
Section: Introductionmentioning
confidence: 99%
“…In another report, Gal-3 silencing in colonic epithelial cells was shown to decrease the transcriptional activity of AP-1 and SP-1 [15][16][17][18][19][20]. Moreover, a decreased expression of ARSB was associated with an increase in the invasiveness of human melanoma cells by reducing Gal-3 binding to C4S [21]. us, the interaction of Gal-3 with glycosylated components of the tumor microenvironment, such as GAGs, may form a physical and functional scaffold having an important role in cancer biology [14,22].…”
Section: Introductionmentioning
confidence: 90%
“…ese data suggested that Gal-3 plays a central role, at least in part, in the structural organization of tissues acting as a physical barrier to control cell dissemination. Indeed, a decreased expression of Gal-3 is usually observed during breast cancer progression, while cells embolized in the tumor vasculature present high levels of Gal-3, which indicates that Gal-3 maintains the cohesion between the tumor cells until they find a fertile soil to establish a future metastatic seed [21,[24][25][26]. Although the role of Gal-3 in the maintenance of a tumorigenic phenotype by breast carcinoma cells has been previously demonstrated [27], its role in the tumor biology of breast cancer progression and metastasis is still controversial.…”
Section: Introductionmentioning
confidence: 99%